Appearance comparison and other appearance-related influences on body dissatisfaction in everyday life. (March 2019) - Fuller-Tyszkiewicz, Matthew; Chhouk, Julie; McCann, Lorie-Ann; Urbina, Geovanny; Vuo, Hao; Krug, Isabel; Ricciardelli, Lina; Linardon, Jake; Broadbent, Jaclyn; Heron, Kristin; Richardson, Ben
Highlights: We explored appearance-related predictors of state body dissatisfaction. Upward appearance comparisons predicted increased dissatisfaction. This effect remained after controlling for appearance comments and self-monitoring. Appearance comments also emerged as predictors of state body dissatisfaction. Abstract: Although appearance comparisons, self-monitoring, and appearance-related comments have been linked to body dissatisfaction in prior studies, the combined and unique influences of these variables on state body dissatisfaction in daily life has yet to be explored. The present study addressed this gap, and also evaluated whether these state-based effects were stronger for individuals with trait-level body image disturbances (internalization and body dissatisfaction). Eighty-four women completed baseline measures of trait internalization and body dissatisfaction, and then reported momentary experiences of body dissatisfaction, appearance self-monitoring, appearance-related comments, and appearance-based comparisons at up to 10 random times daily for seven days. Multilevel analyses confirmed that both appearance comparisons and commentary (both negative and positive) were predictive of changes in state body dissatisfaction when modelled individually as well as in a combined (full) model. Appearance self-monitoring was not a significant predictor, either individually or in the full model. These within-person relationships were not moderated by individual differences in trait body dissatisfaction and internalization of appearance standards. Accordingly, experiences of body dissatisfaction in daily life may be a common reaction to negative appearance comments and unflattering comparisons, yet positive comments and/or efforts to avoid appearance-based comparisons may have a positive effect on one's body image.